2020
DOI: 10.1021/acssuschemeng.0c02666
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Degradable Thioimidazolium Poly(ionic liquid)

Abstract: New antibacterial agents are urgently required to fight the emergence of antibiotic-resistant bacteria. We recently synthesized the first thioimidazolium ionene, which has antibacterial properties and can degrade in various media. This dual functionality is crucial in order to limit the environmental impact of these biocides. We have found that our polymer is stronger than benzalkonium chloride (BAC) against Pseudomonas aeruginosa and also readily degrades in the presence of base, while remaining stable in aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Important attention is also given to poly-ionic liquids (PILs), which can be designated to achieve amphiphilicity, thereby allowing the polymer’s rapid and efficient transfer through the lipid bilayer of the bacterial membrane [ 242 ]. It has been documented that PILs with high cation density and long alkyl chains have superior antimicrobial efficacy to their small-molecule counterparts [ 243 ].…”
Section: Future Promising Strategies In Cre Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Important attention is also given to poly-ionic liquids (PILs), which can be designated to achieve amphiphilicity, thereby allowing the polymer’s rapid and efficient transfer through the lipid bilayer of the bacterial membrane [ 242 ]. It has been documented that PILs with high cation density and long alkyl chains have superior antimicrobial efficacy to their small-molecule counterparts [ 243 ].…”
Section: Future Promising Strategies In Cre Treatmentmentioning
confidence: 99%
“…It has been documented that PILs with high cation density and long alkyl chains have superior antimicrobial efficacy to their small-molecule counterparts [ 243 ]. However, the use of PILs is currently limited by bioaccumulation in the environment, and studies are focused on identifying compounds with optimal biodegradability [ 242 ].…”
Section: Future Promising Strategies In Cre Treatmentmentioning
confidence: 99%
“…However, research regarding more broad biocidal ionic liquids have found that activity is correlated with higher molecular weights in general, not necessarily just alkyl chains [31].…”
Section: Ionic Systems As Antiseptic and Disinfectantsmentioning
confidence: 99%
“…Poly(ionic liquids) (PILs) consists of repeating units of polymer backbone and ionic liquid (IL) species [ 13 , 14 ]. Recently, various imidazolium PILs have been synthesized and exhibited high sterilization rates against E. coli and S. aureus , as well as multi-drug resistant bacteria, such as methicillin-resistant Staphylococcus aureus (MRSA) [ 15 , 16 , 17 , 18 , 19 , 20 ]. The imidazolium PILs can serve as the antibacterial agents, and they are gaining more and more attention.…”
Section: Introductionmentioning
confidence: 99%
“…Most reported imidazolium PILs contain chloride, bromide, iodide, zinc, and copperas as counter ions, which could pose a hazard to normal cells [ 15 , 16 , 18 , 19 , 24 ]. Furthermore, few papers reported antibacterial hydrogels with PILs.…”
Section: Introductionmentioning
confidence: 99%